2022
DOI: 10.1371/journal.pone.0274111
|View full text |Cite
|
Sign up to set email alerts
|

Basic personal values in the midst of the COVID-19 pandemic in Italy: A two-wave longitudinal study

Abstract: This study investigated value change during two phases of the COVID-19 pandemic in Italy, one of the most affected countries in the world. The first wave of data was collected in summer 2020, when the virus was on the retreat. The second wave was collected in autumn, at the peak of the second pandemic wave (November 2020). We investigated how Schwartz’s higher-order values changed over the two waves of the study, using economic condition as a predictor of change. We also examined whether value change predicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Regarding political orientation, a comprehensive review by Shushtari et al (2021) shows that political inclinations influenced mask-wearing, with Democrats more likely to use it than Republicans. Relating to personal values, there are several studies (e.g., Bonetto et al 2021;Vecchione 2022) that analyze the relationship between these and prevention behaviors; however, most use the Portrait Values Questionnaire, and therefore comparisons with the moral values of Hunt et al (2022) study are not feasible. Some limitations must be considered regarding the present systematic review.…”
Section: Mask-wearingmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding political orientation, a comprehensive review by Shushtari et al (2021) shows that political inclinations influenced mask-wearing, with Democrats more likely to use it than Republicans. Relating to personal values, there are several studies (e.g., Bonetto et al 2021;Vecchione 2022) that analyze the relationship between these and prevention behaviors; however, most use the Portrait Values Questionnaire, and therefore comparisons with the moral values of Hunt et al (2022) study are not feasible. Some limitations must be considered regarding the present systematic review.…”
Section: Mask-wearingmentioning
confidence: 99%
“…There is evidence that other cognitive factors influence adherence to norms and rules. Among those factors, the role of "personal values" has been addressed during COVID-19, mainly: conservation, self-enhancement, openness-to-change values (Bonetto et al 2021;Daniel et al 2022;Potocan and Nedelko 2023;Vecchione 2022), self-transcendence (Daniel et al 2022;Vecchione 2022), religious belief, government satisfaction, and individual freedom (Lyu et al 2022). Also "age" has been studied as a determinant of adherence with COVID-19 public health preventive measures, with young adults identified as a group with low adherence to COVID-19 protective behaviors (WHO 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Against this backdrop, the COVID-19 pandemic allows us to study how a large-scale social and economic shock affects the prevalence of emancipative values on both the societal and the individual levels. Some recent studies observed a decline in emancipative orientations (Akaliyski et al, 2023), an significant rise of institutional trust Reeskens et al, 2021), and specifically of confidence in political authority (Foa & Welzel, 2023), an increase in conservation values (Bojanowska et al, 2021;Daniel et al, 2022;Vecchione, 2022), and a decrease in Schwartz's openness to change and self-transcendence values 2 (Bonetto et al, 2021;Daniel et al, 2022) during the pandemic. Based on this, we expect that the pandemic led to a decrease in the average prevalence of emancipative values in Russia, and personal negative experience during the pandemic could lead to a decline in individual support for emancipative value orientations among the Russian population.…”
Section: Emancipative Values and Cultural Modernizationmentioning
confidence: 99%
“…Initial studies suggest that the COVID-19 pandemic, as an extreme event, shifts individuals' value systems [12][13][14][15][16]. All studies claim they cannot generalize their implications as they focus on people from a specific country, and the pandemic hit countries differently.…”
Section: Introductionmentioning
confidence: 99%
“…All studies claim they cannot generalize their implications as they focus on people from a specific country, and the pandemic hit countries differently. More data is needed to better understand the changes in individuals' value systems caused by the pandemic, better assess discrepancies between study results, and draw firm conclusions [16]. Existing studies recommend looking at other countries, a longer period before and after the outbreak of the pandemic [13], and using other data collection methods such as reports on social values [14] or the lexical analysis of texts in newspapers [17].…”
Section: Introductionmentioning
confidence: 99%